Lightning Response of Multi-Port Grids Buried in Dispersive Soils: An Approximation versus Full-wave Methods and Experiment - Sajjadi, S. S.; Ostadzadeh, S. R. (Advanced Electromagnetics, 2019)
In this paper, application of multi-conductor transmission line model (MTL) in transient analysis of grounding grids buried in soils with frequency-dependent electrical parameters (dispersive soil) is investigated. In this modeling approach, each set of parallel conductors in the grounding grid is considered as a multi-conductor transmission line (MTL). Then, a two-port network for each set of parallel conductors in the grid is then defined. Finally, the two-port networks are interconnected depending upon the pattern of connections in the grid and its representative equations are then reduced. Via solving these simplified equations, the transient analyses of grounding grids is efficiently carried out. With the aim of validity, a number of examples previously published in literature are selected. The comparison of simulation results based on the MTL shows good agreement with numerical and experimental results. Moreover, in despite of numerical methods computational efficiency is considerably increased.